Desenvolvimento de bebida láctea achocolatada de cabra contendo Bifidobacterium lactis, inulina e Frutooligossacarídeos - Silveira, Ericka Oliveira da (2014)
The development of functional goat dairy products is a viable alternative to add value to goat milk and to popularize new functional foods, considering the growing demand for foods with high nutritional quality, tasteful and promoters of well-being and health. This study aimed to produce chocolate goat dairy beverages with the probiotic Bifidobacterium lactis and evaluate the effects of goat cheese whey and prebiotics (inulin and oligofructose) on the physicochemical parameters and sensory features of the beverages during 28 days of refrigerated storage. Seven formulations of dairy beverages were analyzed for protein, fat, ash and lactose immediately after production, and submitted to physicochemical analysis (titratable acidity, total solids, pH, syneresis, apparent viscosity) and microbiological analysis, including B. lactis viability, after 1, 7, 14, 21 and 28 days. Sensory acceptability was determined after 14 days. All formulations had decreased pH and concomitant increase in the acidity during refrigerated storage. Beverages made with the lowest amounts of whey (F1 and F3) had greater decrease in pH from 14 days of storage. The apparent viscosity increased up to 21 days for all formulations, and up to 28 days for F4 (6 g 100 g - 1 prebiotics and 45 mL 100 mL -1 whey), possibly related to the higher amounts of whey and inulin. B. lactis showed counts between 6 and 8 log CFU mL-1. F4 presented the highest average in sensory attributes flavor and aroma. Apparently, larger amounts of prebiotics and whey in the beverage enhance the flavor perception, which may be a consequence of the intensification of cocoa flavor and / or lower acidity perception. Thus, F4 was the formulation that best represented the desirability profile chosen for the probiotic chocolate goat dairy beverage as best viscosity and improved sensory features.